Odpowiedź :
Odpowiedź:
a)[tex]\frac{x}{3}[/tex] + 1 = [tex]\frac{5}{6}[/tex] + [tex]\frac{x}{2}[/tex]/ · 6
2x+6=5+3x
2x-3x=5-6
-x=-1/:-1
x=1
b)[tex]\frac{2x-3}{4}[/tex] = [tex]\frac{1}{2}[/tex] +x/ ·4
2x-3= 2+ 4x
2x-4x=2+3
-2x=5/:-2
x= -[tex]\frac{5}{2}[/tex]
c)[tex]\frac{x+2}{9}[/tex] + [tex]\frac{x-1}{3}[/tex] = 1/·9
x+2+3x+3=9
x+3x=9-2-3
4x=4/:4
x=1
d)[tex]\frac{2x+3}{5}[/tex]= [tex]\frac{2-x}{3}[/tex] + x/·15
6x+9= 10-5x+15
6x+5x=10+15-9
11x=34
x=[tex]\frac{34}{11}[/tex]
e)[tex]\frac{3x-5}{2}[/tex] - [tex]\frac{5x-1}{10}[/tex]=0/·10
25x-25-5x-1=10
25x-5x=10+25-1
20x=34
x=1,7
f)[tex]\frac{x}{2}[/tex]=[tex]\frac{2}{5}[/tex](4-x)-4/·10
5x=8-4x-40
5x+4x=8-40
9x= -32
x=-[tex]\frac{32}{9}[/tex]
g)
[tex]\frac{2x-1}{5}[/tex] - [tex]\frac{x-2}{2}[/tex] = 0,7x/·10
4x-4-5x+10=7x
4x-5x-7x=4-10
-8x= - 6/:-8
x=[tex]\frac{6}{8}[/tex]
h)2x - [tex]\frac{3x+5}{4}[/tex]= -[tex]\frac{1}{4} x[/tex] - 1 /·4
8x-3x+5=-x-4
8x-3x+x=-4-5
12x=-9
x= -[tex]\frac{9}{12}[/tex]
Szczegółowe wyjaśnienie: